A Study To Compare The Serum Cytokines Level With The Immuno-Histochemistry (Ihc) In Breast Cancer Patients - Raju, Raju; Bhat, Sajad; Monika, Monika; Tripathi, Sandeep (Journal of Neonatal Surgery, 2025)
Introduction: Breast cancer is the most frequently diagnosed cancer and is the foremost cause of death among women worldwide. The cytokine concentrations in the blood can be used as a predictor of prognosis and immunity in the case of cancer. This study was planned to compare the serum cytokines level with the Immuno-histochemistry (IHC) among patients with clinically suspected breast malignancy. Material & Methods: This was a prospective study. It will include all breast cancer patients in NIMS University Rajasthan Jaipur. All study subjects undergone a detailed clinical assessment, including medical history and family history of cancer, physical examination of the breast and axilla, radiological imaging and biopsy for histopathological confirmation. Quantification of cytokines was performed using enzyme-linked immunosorbent assay (ELISA) kits specific to each cytokine. Results: The serum levels of pro-inflammatory cytokines IL-2, IL-6, IL-12, IFN-γ, IFN-α, and IFN-β were significantly elevated in the malignant group compared to the benign group (p < 0.001). Similarly, the anti-inflammatory cytokines IL-4, IL-10, and IL-11 also showed a significant increase in confirmed malignant cases (p < 0.01). Elevated levels of IL-6, IL-10, and IL-12 were significantly associated with HER2-positive tumors (p = 0.001). Triple-negative breast cancer (TNBC) cases (n = 11) demonstrated the highest levels of IFN-γ and IL-6, suggesting a more inflammatory microenvironment. Conclusion: The altered serum cytokine profiles observed in this study support the hypothesis that systemic inflammation is intricately linked with breast cancer development. Both pro- and anti-inflammatory cytokines may serve as valuable adjuncts in early detection, prognosis, and therapeutic monitoring of breast malignancy.